PEMBERIAN EKSTRAK N-HEKSANA DAUN PEPAYA JEPANG (Cnidoscolus aconitifolius) TERHADAP MORTALITAS LARVA Anopheles sp. - Salsabil Hidayatul Aisyah; Emantis Rosa; Nuning Nurcahyani; Hendri Busman (BULLET : Jurnal Multidisiplin Ilmu, 2026)
Malaria remains a public health problem in Indonesia. Controlling malaria vectors (Anopheles sp.) using synthetic larvicides carries the risk of developing resistance and environmental pollution, requiring natural alternatives from Japanese papaya leaves (Cnidoscolus aconitifolius). This study aimed to analyze the effect of concentration and exposure time of n-hexane extract of Japanese papaya leaves on mortality of Anopheles sp. larvae and to determine LC50 and LT50 values. The experimental method used Completely Randomized Design (CRD) with six concentrations (0%; 0.5%; 0.75%; 1%; 1.25%; and 1.5%) and four replications, using 20 third instar larvae for each experimental unit. Mortality observations were conducted after 6, 12, 24, 36, and 48 hours of exposure, while morphological changes were observed using a digital microscope. Data were analyzed using One-way ANOVA, LSD, and probit analysis. The results showed that n-hexane extract had a significant effect (p < 0.05) on larval mortality. 100% mortality was achieved at a concentration of 1.5%, followed by a concentration of 1.25% at 95% after 48 hours. The LC50 value obtained was 1.088% at 24 hours of exposure, while the fastest LT50 was at a concentration of 1.25% for 16.34 hours. Exposure to the extract also induced morphological damage, including body darkening, swollen thorax, severed digestive tract, and transparent body. Therefore, n-hexane extract of Japanese papaya leaves has the potential to be developed as an environmentally friendly natural biolarvicide.